Regulation of ocular blood flow during increases of arterial blood pressure. Issue 6 (June 1994) - Michelson, G; Groh, M; Gründler, A
Abstract : The blood flow in the uvea in cats and monkeys during acute increases of arterial blood pressure is well controlled by a sympathetic mechanism protecting the eye from overperfusion. Ocular macrocirculation (ophthalmic artery) and ocular microcirculation (iris) were examined in 22 healthy subjects during acute increases of arterial blood pressure induced by physical exercise (125 W). With a data acquisition and storage software in real time mode several parameters of ocular perfusion and systemic functions were measured simultaneously. Blood flow parameters were measured in the ophthalmic artery by pulsed Doppler sonography and in the iris by laser Doppler flowmetry. Systolic, diastolic, and mean velocities of the ophthalmic artery peak velocity pulse curve, the ophthalmic artery mean velocity pulse curve, and the iris velocity pulse curve were estimated off line. The ophthalmic artery mean velocity pulse curve resembles the integrated velocity of all erythrocytes in the vessel including the slowly running cells near the vessel wall. The iris velocity pulse curve was calculated by a special statistic procedure (ALDF). After exercise there was a significant increase in systolic and diastolic blood pressure and heart rate. The pulse curve of the ophthalmic artery showed significantly increased systolic and decreased diastolic velocities. The vascular resistance of the branches of the ophthalmic artery increased significantly. The iridal vasculature showed no significant change in blood cell velocity but an increased vascular resistance. It was observed that the elevated perfusion pressure was associated with an increased vascular resistance and a constant mean blood velocity in the ophthalmic artery and iridal vessels. The parallel elevation of vascular resistance and blood pressure during exercise may be the reason for a constant blood flow in the ophthalmic artery and the iris. This may be accounted for by a sympathetic mechanism for protecting the eye from overperfusion.